Therapeutic Doses of Antioxidants Inhibit the Growth and Enhance the Effects Chemotherapy and Radiation Therapy on Cancer Cells by Blocking the Uptake and Metabolism of Glucose and Glutamine - Prasad, Kedar N. (Archives of Business Research, 2024)
Chemotherapy and radiation therapy have produced increased 5-year survival rate in majority of cancers; however, acute side-effects during treatment and late adverse effects after these therapies remain a major concern of oncologists. To improve further 5-year survival rate and reduce acute and late adverse effects of therapies, a new non-toxic biological approach is needed. Experimental data for such an approach was available for over 25 years. For example, therapeutic doses of antioxidants inhibit the growth of cancer cells and enhances the growth-inhibitory effects of chemotherapeutic agents and x-irradiation on cancer cells but not on normal cells. These exciting observations failed to draw any attention from oncologists, because mechanistic data on therapeutic doses was not available until now. The mechanistic data on preventive doses of antioxidants suggested that they scavenge free radicals. Since one of the mechanisms of action of chemotherapy and radiation therapy on cancer cells is mediated by free radicals, oncologists fear that supplementation with antioxidants may reduce the effectiveness of cancer therapies by neutralizing free radicals. Cancer cells require glucose and glutamine for their survival and proliferation. This review briefly describes the effects of therapeutic doses of antioxidants alone and in combination with chemotherapy and radiation therapy on the growth of neoplastic cells and normal cells. It also presents evidence to show that such doses of antioxidants reduce the uptake and metabolism of glucose and glutamine in cancer cells. We propose that therapeutic doses of multiple antioxidants can selectively kill cancer cells and enhance the growth-inhibitory effects of therapeutic agents on cancer cells without affecting normal cells by inhibiting the uptake and metabolism of glucose and glutamine.